Agglomeration economies and the location of new information and communication technology (ICT) firms in the Netherlands - Oedzge Atzema; Frank van Oort (European Regional Science Association (ERSA), 2002)
In 2000, the world wide, rapid employment growth in the ICT-sector came to an end. Knowledge-intensive ICT-firms and -sectors in the Netherlands confirmed to this negative development trend as well. The life-cycle of the ICT-sector appears to reach a new phase of development, dominated by saturation of demand and enforced competition. This might affect the localised growth in the ICT-sector as well. According to evolutionary interpretations of agglomeration theory, one expects that new ICT firms start up in knowledge intensive, urban setting in order to gain from localised knowledge spillovers. The recent empirical literature is not unambiguous clear upon the role of intra- and intersectoral (specialisation or sectoral diversity based) agglomeration circumstances that determine firm formation, growth and survival patterns. In later stages of sectoral development, three kinds of spatial developments are expected from the geographical growth literature: (1) a cummulative causation based process of growth within the preliminary urban settings; (2) a dispersion process towards suburban and adjacent rural regions based on physical network and proximity conceptualisations, (3) spatial growth transmittance and firm dispersion based on functional network spatial relationships which are predominantly non-contiguous in character. For the latter category of spatial economic dynamics, the degree of urbanisation, accessibility, regional labour market- and national zoning spatial regimes are assumed to be leading spatial conceptualisations. A favourable macro-economic growth perspective, as present in the Netherlands during our research period, is assumed to speed up (and condition) spatial economic dispersal patterns. To test these spatial growth transmittance and firm dispersal hypotheses we analyse the components of growth (new firm formation, survival and growth in incumbent firms) of a large dataset of in total 36,000 ICT firms in the Netherlands for the period 1996-2000. The papers empirically distinguishes in-situ urban growth, contiguous relations in growth patterns (starting on an initially low, intra-urban spatial scale) and heterogeneous (non-contiguous) spatial research designs. Conclusions are drawn in relation to the recent agglomeration and economic growth literature.
Keywords: 330